Analisis Yuridis Penentuan Sisa Utang Eksekusi Hak Tanggungan (Putusan 78/Pdt.G/2024/PN Tjk jo. 120/PDT/2024/PT TJK) - Bagus Indrawan; Depri Liber Sonata; Dita Febrianto; Sepriyadi Adhan S; Selvia Oktaviana (Lembaga Yasin AlSys, 2026)
Although the efficiency of credit settlement through the parate execution mechanism of Hak Tanggungan has been widely discussed, studies that specifically examine disparities in judicial decisions arising from the lack of transparency regarding the breakdown of outstanding debt prior to auction remain limited. This study aims to analyze, from a juridical perspective, the judicial reasoning used to determine the remaining debt in the execution of Hak Tanggungan in Decision Number 78/Pdt.G/2024/PN Tjk jo. Number 120/PDT/2024/PT TJK. The research adopts a normative juridical approach with a statute and case approach design, using primary and secondary legal materials selected through purposive sampling. Data were collected through library research and document study, then analyzed qualitatively-normatively using deductive reasoning. The findings show that, formally, the High Court progressively annulled the District Court’s inadmissible (N.O) decision in order to separate the unlawful act (Perbuatan Melawan Hukum, PMH) dispute from the legal regime governing auction buyer protection. However, substantively, the appellate judges became trapped in procedural formalism by validating the auction solely on the basis of evidence of the dispatch of a demand letter, without scrutinizing the absence of a detailed breakdown of the debtor’s remaining debt. These results contribute to the development of substantive justice theory by clarifying the limits of a creditor’s objective good faith and affirming that transparency regarding the details of outstanding debt is an indispensable precondition for the validity of security enforcement. The study concludes that clearer jurisprudential guidelines from the Supreme Court are needed to standardize judicial assessment of Hak Tanggungan execution and recommends strengthening transparency and prudential principles in banking practice. The implications include theoretical contributions to the literature on security law and banking prudence, practical implications for the judiciary, and opportunities for further empirical research on the sociological impact of unilateral execution.